UNSAFE ACTION PADA PEKERJA BAGIAN MAINTENANCE PT SEMEN PADANG UNIT PABRIK DUMAI RIAU - Yeni Herlina; Wenny Murdina Asih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Maintenance is an activity to maintain factory equipment facilities, make repairs or adjustments / replacements needed so that there is a satisfactory production operating condition in accordance with what is planned. The maintenance department is in charge of maintaining the machines and other tools related to the production process. The purpose of this research is to see the description of unsafe action on the workers of the Maintenance Division of PT. Semen Padang Dumai Factory Unit. The design of this study uses descriptive quantitative methods, namely describing or describing the unsafe action of the maintenance workers at PT. Semen Padang Dumai Factory Unit Riau Province. The sample used in this study is total sampling, totaling 19 respondents. The results of this study indicate as many as 63.15% of the Maintenance Division workers have done unsafe action. Among them are lifting weights with awkward body positions such as lifting in a stooped position, joking with colleagues at work, and having repaired work equipment that is currently operating.